2017
DOI: 10.3892/ol.2017.7548
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of cancer tissues in Chinese patients with gastric cancer by high-throughput sequencing

Abstract: Gastric cancer (GC) is the fifth most common malignancy and the third leading cause of cancer-associated mortality worldwide. Therefore, there is a requirement to identify sufficiently sensitive biomarkers for GC. Genome-wide screening of transcriptome dysregulation among cancerous and normal tissues may provide insights into the underlying molecular mechanisms of GC initiation and progression. At present, high-throughput sequencing techniques have begun to innovate biomedical studies. The RNA-seq method has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Therefore, enhancing the effects of chemotherapy by seeking new specific therapeutic targets is important for improving the prognosis of gastric cancer. Recently, a number of studies demonstrated that molecular biology and gene technology advancements such as high-throughput sequencing have offered new opportunities to research the molecular mechanisms underlying gastric cancer, and various novel targets have been discovered [18][19][20][21]. For example, Liu et al noted that a potential tumor promoter, NETO2, was upregulated in gastric cancer tissues and could promote the invasion and metastasis of gastric cancer through TNFRSF12Amediated activation of the PI3K/AKT/NF-κB/Snail axis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, enhancing the effects of chemotherapy by seeking new specific therapeutic targets is important for improving the prognosis of gastric cancer. Recently, a number of studies demonstrated that molecular biology and gene technology advancements such as high-throughput sequencing have offered new opportunities to research the molecular mechanisms underlying gastric cancer, and various novel targets have been discovered [18][19][20][21]. For example, Liu et al noted that a potential tumor promoter, NETO2, was upregulated in gastric cancer tissues and could promote the invasion and metastasis of gastric cancer through TNFRSF12Amediated activation of the PI3K/AKT/NF-κB/Snail axis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Annotated transcripts are used to study differentially expressed genes while non-mapped reads can be analyzed to study fusion genes or viral transcripts. Transcriptome sequencing data can also be used to define novel transcripts leading to discovery of neoantigens [13][14][15] .…”
mentioning
confidence: 99%
“…In the present work, comprehensive survival analysis and Cox regression analysis found that upregulation of DPT and LRFN4 correlated with good prognosis in gastric cancer patients. DPT is significantly downregulated in gastric cancer tissues [ 48 ], and it may contribute to oral cancer metastasis [ 49 ]. DPT is also involved in the inhibition of proliferation of keratinocytes, osteosarcoma cells, and papillary thyroid carcinoma cells in mice [ 50 ].…”
Section: Discussionmentioning
confidence: 99%